Psychological characteristics of opioid dependence in remission: existential aspect - E. B. Karpova; A. V. Kipnis; L. V. Kuznetsova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
The article adduce the results of a study of real existential experiences, such as attitudes towards loneliness, freedom, death, the meaning of life, as well as a temporary lifespan and viability in with opioid dependecе patients who are in a period of unstable remission. The study involved 31 patients of the St. Petersburg.Drug Treatment Hospital who were in a period of unstable remission and 30 respondents with similar socio-demographic characteristics, but without drug dependence. Comparison of the data showed significant differences in future time perspective and indicators of motivation of opioid-dependents and control group respondents. The negative attitude towards loneliness and the higher level of his experience in drug addicts attracts attention.